Genotypic and phenotypic characterisation of enteroaggregative Escherichia coli from children in Rio de Janeiro, Brazil. - Fernanda L S França; Timothy J Wells; Douglas F Browning; Raquel Tayar Nogueira; Felipe Silva Sarges; Ana Claudia Pereira; Adam F Cunningham; Kely Lucheze; Ana Claudia Paula Rosa; Ian R Henderson; Maria das Graças de Luna (PLoS ONE)
Enteroaggregative Escherichia coli (EAEC) is a significant cause of diarrhoeal illness in both children and adults. Genetic heterogeneity and recovery of EAEC strains from both healthy and diseased individuals complicates our understanding of EAEC pathogenesis. We wished to establish if genetic or phenotypic attributes could be used to distinguish between strains asymptomatically colonising healthy individuals and those which cause disease. Genotypic screening of a collection of twenty four EAEC isolates from children with and without diarrhoea revealed no significant differences in the repertoire of putative virulence factors present in either group of strains. In contrast, EAEC strains from phylogroup A were more strongly associated with asymptomatic groups whereas strains from phylogroup D were more associated with cases of diarrhoea. Phenotypic screening revealed no differences in the ability of strains from either cohort of children to form biofilms, to adhere to and invade cells in tissue culture or to cause disease in the Caenorhabditis elegans model of infection. However, the latter assay did reveal significant reduction in nematode killing rates when specific virulence factors were deleted from human pathogenic strains. Our results suggest that current models of infection are not useful for distinguishing avirulent from pathogenic strains of EAEC but can be useful in studying the effect of specific virulence factors.